2009
DOI: 10.1073/pnas.0905209106
|View full text |Cite
|
Sign up to set email alerts
|

A distinctive role of the leukotriene B 4 receptor BLT1 in osteoclastic activity during bone loss

Abstract: Although leukotriene B4 (LTB4) is produced in various inflammatory diseases, its functions in bone metabolism remain unknown. Using mice deficient in the high-affinity LTB4 receptor BLT1, we evaluated the roles of BLT1 in the development of two bone resorption models, namely bone loss induced by ovariectomy and lipopolysaccharide. Through observations of bone mineral contents and bone morphometric parameters, we found that bone resorption in both models was significantly attenuated in BLT1-deficient mice. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 64 publications
(66 reference statements)
0
42
2
Order By: Relevance
“…Finally, BLT 1 R knockout mice are protected in models of both collagenand K/BxN serum-induced arthritis (Kim et al, 2006a;Shao et al, 2006;Mathis et al, 2010), discussed in detail below. In this context, BLT 1 R knockout mice displayed a decrease in bone resorption induced by either LPS or ovariectomy (Hikiji et al, 2009).…”
Section: E Blt Receptor Functional Analysis Through Altered Gene Expmentioning
confidence: 99%
“…Finally, BLT 1 R knockout mice are protected in models of both collagenand K/BxN serum-induced arthritis (Kim et al, 2006a;Shao et al, 2006;Mathis et al, 2010), discussed in detail below. In this context, BLT 1 R knockout mice displayed a decrease in bone resorption induced by either LPS or ovariectomy (Hikiji et al, 2009).…”
Section: E Blt Receptor Functional Analysis Through Altered Gene Expmentioning
confidence: 99%
“…The resultant cDNA was amplified by PCR. The protocol and sequences of primers used to measure Ltb4r1, arachidonate 5-lipoxygenase (Alox5), and Actb (also known as b-actin) levels were described previously (15).…”
Section: Rt-pcr Analysismentioning
confidence: 99%
“…These observations suggest that increased bone formation or decreased bone resorption may occur in the absence of the 5-LO enzyme and suggest that 5-LO and its metabolites may act as regulators of bone metabolism. Although some studies indicated that LTB4 functions by inhibiting bone formation and stimulating osteoclastic bone resorption (15)(16)(17), little is known about the roles of 5-LO and its metabolites in osteoclast differentiation. In the current study, we clarified their critical roles and intracellular signaling pathways in osteoclast differentiation.…”
mentioning
confidence: 99%